Assessment of Body Mass Index and Nutritional Status in Pulmonary Tuberculosis Patients - Sultan, Kassim M.; Alobaidy, Muhammed W.; AL-Jubouri, Adnan M.; Abbas Naser, Azher; AL-Sabah, Hamza A. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Pulmonary tuberculosis is a chronic infectious disease which affects nutritional status of the patients. The presence of poor nutritional status in pulmonary tuberculosis patients has been one of the most important determining factor in recommending adjuvant nutrient therapy to prevent oxidative stress and further complication.Objective: This study was designed to assess the nutritional status and body mass index of pulmonary tuberculosis patients.Patients and methods: During the period 1st of June 2010 to 30th of May 2011, a prospective study was done on 60 patients with active pulmonary tuberculosis and 60 controls.Levels of total protein (TP), albumin (ALB.), triglyceride (TG), total cholesterol (TC), high density lipoprotein cholesterol (HDLC), low density lipoprotein cholesterol (LDLC), and body mass index (BMI) were measured.Results: The mean levels of TP (59.5 ± 0.8g/dl), ALB (23.4 ± 1.8g/dl), TC (138.7 ± 4.9mg/dl), HDLC (32.2 ± 4.0mg/dl), LDLC (86.5 ± 1.3mg/dl) and TG (62.4 ± 1.3mg/dl) were significantly lower while the level of globulin (36.2 ± 1.2g/dl) was significantly higher in pulmonary tuberculosis patients when compared with controls (TP=81.2 ± 4.5g/dl; ALB= 50.0 ± 4.0g/dl; TC = 213.5 ± 26.8mg/dl; HDLC = 57.4 ± 8.5mg/dl; LDLC = 161.1 ± 28.3mg/dl; TG= 148.5 ± 37.1mg/dl; globulin = 31.4 ± 1.7g/dl respectively). (P